Concussion in Ladies Gaelic Football: Self-reported History, Clinical Profiles, and Management Behavior. Issue 2 (5th March 2023) - Leahy, Róisín; Rochfort, Keith D.; Whyte, Enda; Kontos, Anthony P.; Collins, Michael W.; O'Connor, Siobhán
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To describe the prevalence, characteristics, and management behavior of self-reported sport-related concussion (SRC) in Ladies Gaelic Football (LGF) players. Design: Cross-sectional study. Setting: Online survey distributed to LGF clubs throughout Ireland. Participants: Elite and nonelite adult LGF players (n = 657). Interventions: Participants were recruited by convenience sampling and answered an online survey. Questions on demographic characteristics, SRC history, symptoms, injury characteristics, and management behavior after SRCs that occurred while playing LGF during the previous season were included. Main Outcome Measures: Overall concussion history, occurrence of an SRC during the previous LGF season, clinical profile scores, characteristics (eg mechanism and setting), and management behavior (eg following a graded RTP program) after SRCs that occurred during the previous season. Results: Approximately one-fifth (17.5%) of participants sustained a suspected or diagnosed SRC during the previous season, which was higher among elite (26.1%) than nonelite (15.3%) players ( P < 0.01). The highest scoring clinical profiles were the ocular and migraine profiles. Only 3.5% of respondents adhered to all SRC management recommendations. Although players who reported a medically diagnosed versus a suspected SRC more often followed these guidelines, SRC management beyond the initial phase of injury remained inadequate. Conclusion: SRC is common in LGF; however, adherence to recommended management guidelines is poor, even among players who receive medical assistance. In particular, few LGF athletes receive clinical concussion care beyond the initial diagnosis and acute management phase. Further research is needed to examine the underlying reasons for poor SRC management in LGF, which will guide the development of future sport-specific interventions.